A Comparison of Magnetic Resonance Imaging and Electroneuromyography for Denervated Muscle Diagnosis. Issue 3 (May 2017) - Tepeli, Betül; Karataş, Metin; Coşkun, Mehmet; Yemişçi, Oya Ümit
Abstract : Purpose: The aim of this study was to evaluate the diagnostic value of magnetic resonance imaging (MRI) for muscle denervation due to focal lesions of the median nerve and to compare electrophysiological findings with MRI findings. Methods: Twenty-six patients with electrophysiological studies diagnosed for focal lesions of the median nerve were included in this study. Electrophysiological studies and MRI were conducted on 34 patients' hands. Patients' hands were divided into two groups based on edema findings revealed by the MRI: group 1 (edema-negative group; n = 24) and group 2 (edema-positive group; n = 10). Results: Positive correlations were found between the existence of edema in MRI and fibrillation, positive sharp waves, denervation, and the level of reduced recruitment pattern. In median nerve conduction studies, amplitude of compound muscle action potential and palm-to-wrist segment mixed-nerve action potentials were significantly lower, and also the third-digit wrist sensory nerve conduction velocity and mixed-nerve palm–wrist conduction velocity were significantly slower in group 2. Conclusions: For muscle denervation resulting from median nerve lesions, MRI findings correlated with electrophysiological findings; further study is required for the use of MRI.